Deconstructing and reconstructing diversity in client-provider-relationships of social work - Lars Alberth; Ellen Kollender; Anke Karber; Philipp Sandermann; Birte Siem (Social Work and Society, 2025)
Diversity and reflections on diversity impact client-provider-relationships of social work on different levels, ranging from institutionalized programs to interpersonal practices to individual expectations, cognitive make-ups and emotional experiences. However, the implications of diversity and its reflections in social work practice are still far from being sufficiently empirically researched. Depending on the precise situation, diversity may be directly involved in the forms of categorizations, valorizations, or social identities that influence professional social work from diagnostical judgement to service delivery. But it may also be pivotal as a physical or organizational context factor that influences decision-making, leads to more (a-)symmetrical and (un-)just distributions of resources, (in-)visibility of individuals, and power. Seeing client-provider-relationships through the lens of diversity shows the complexity, richness and fundamentally social quality of social work.